New frontiers in quantitative methods in informatics : 7th Workshop, InfQ 2017, Venice, Italy, December 4, 2017, Revised selected papers /: 7th Workshop, InfQ 2017, Venice, Italy, December 4, 2017, Revised selected papers. (2018) - Unknown
No abstract available